Amiss, a miss, a near miss. Issue 2 (8th August 2015) - Wincek, John C.
Abstract : Catastrophic incidents, while common in the world, are rare events to any single facility or even company. Were anyone to count catastrophic incidents to measure Process Safety performance, it is likely the facility would be gone before they counted to two. We look instead to Near Miss incidents as one measure of Process Safety performance. We count them and measure their frequency. We implement corrective actions to prevent reoccurrence. We look beyond the specific incident to apply the lessons in other areas. Most importantly, we look for faults in our management systems that permitted the near miss to occur. Defining near misses, identifying their occurrence, and fully learning the lessons they can teach us can be a difficult undertaking. Simple communication of these incidents can be problematic. And, learning lessons from an incident occurring at another facility can challenge even the broadest‐minded people. This article will describe the learning process that has evolved at one specialty chemical company. It will include definitions of specific types of near misses, how data are gathered and communicated, and information on the number and type of incidents occurring. The reader will gain ideas on how to classify and collect data on specific near miss incidents, and ways to communicate the information throughout a company. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 137–142, 2016